Students’ Perspectives on Using Natural Reader to Support TOEFL Listening Practice: An Experience-Based Study - Fitria, Tira Nur (Langue (Journal of Language and Education), 2025)
This research describes students’ perspectives and experiences in using Natural Reader to support learning TOEFL listening practice. This research uses a descriptive qualitative method. Students generally have a good understanding of how to use Natural Reader for TOEFL listening practice, appreciating its key features like adjustable speed, voice options, and offline use. While feedback on its features is mostly positive, some find certain functions less effective or challenging, and there are concerns about the AI voice’s naturalness and the limitations of the free version. Natural Reader is viewed as helpful for improving listening skills, boosting confidence, aiding vocabulary, and maintaining focus, though some question its effectiveness with more complex listening tasks. The tool is praised for clear audio, flexibility, and user-friendliness, with many motivated to continue using it and recommending it for TOEFL preparation. However, drawbacks include a monotonous voice, potential boredom with prolonged use, technical issues, and a preference among some students for original audio or teacher guidance. Overall, Natural Reader positively influences motivation and confidence, reduces anxiety, and is seen as suitable for both self-study and classroom use, though some learners still prefer alternative materials. Several studies have explored the use of Text-to-Speech (TTS) technology to enhance English listening skills. Overall, these studies confirm the growing effectiveness and versatility of TTS in listening comprehension development.